The Responsibility of Notary Agreement of The Truth Under Hand Notarized as Evidence in The Process of Trial in Court - Eka Daryanti; Mochammad Ipnu Wardani; Gunarto Gunarto (Jurnal Akta, 2018)
The legal consequences under the hand agreement validated by notaries who are connected with the responsibility of Notary if the agreement be used as evidence in court. This study aims to analyze the responsibility of the Notary to the truth of the under the hand agreement that was authorized by the Notary, to analyze the legal consequences of the agreement under hand, legalized by the Notary as evidence in evidence during the trial. From the results of this research is that: 1) responsibility to the truth Notary under the hand agreement that was authorized by the Public Notary. Notary is the only guarantee certainty regarding the date, identity and signature of the parties to the agreement. Notary ensures certainty at the time of signing the agreement, that the parties who signed the agreement is valid and not others, the parties who signed properly attended and have been aware of the contents in the agreement because it is read by the notary, so that the parties can not deny, 2) the legal consequences under the hand agreement, legalized by the Notary as evidence in court proving that the under the hand agreement only give legal effect to the advantage of a perfect proofing to whom sipenadatangan about to give evidence, while against the third party free pembuktianya legal consequences. If the authentic act has the strength of evidence was perfect, under the hands of the legal consequences certificate of proof rests with the judge to consider.Keywords: Responsibility; Under the Hands Agreement; Legalization.